Color Doppler ultrasound and computed tomographic angiography for perforator mapping in DIEP flap breast reconstruction revisited: A cohort study. Issue 10 (October 2019) - Mijuskovic, B.; Tremp, M.; Heimer, M.M.; Boll, D.; Aschwanden, M.; Zeindler, J.; Kurzeder, C.; Schaefer, D.J.; Haug, M.D.; Kappos, E.A.
Summary: Introduction: Preoperative imaging by Computed Tomographic Angiography (CTA) has been promoted a gold standard tool for perforator mapping in abdominally based microsurgical breast reconstruction, while Color Doppler Ultrasound (CDU) has lost its popularity. As the CTA X-ray exposure might have long-term consequences for patients, CDU has regained importance for preoperative workup in our center. Our aim was to revisit the role of CDU by comparing the reliability of CDU and CTA in predicting intraoperative perforator selection. Materials and Methods: We performed a retrospective chart review study of patients who underwent microsurgical breast reconstructions with DIEP flaps at our institution. Both CTA and CDU were performed prior to the surgery, and both imaging entities were thoroughly examined by the surgical team. Perforator identification, number, size, and location were assessed and correlated with CTA and CDU data and with intraoperative findings. Results: We identified 98 patients who received 125 DIEP flap surgeries. A significantly stronger correlation was found between CDU and intraoperative findings of perforator detection and size ( p <0.0001) and selection ( r = 0.9987, CI 0.9981–0.9991, p < 0.0001 and r = 0.01, CI -0.18–0.2, p = 0.91, respectively), when compared with CTA data. If none of the preoperative imaging studies matched intraoperative perforator selection, an association with a higher incidence of flap loss (Odds ratio 4.483, CI 0.5068–39.65, p = 0.2171) was found. Conclusions: Our data suggests that CDU might regain relevance as a safe and reliable preoperative imaging study, without the risk and potential consequences of X-ray exposure. Preoperative imaging tools like CDU and CTA should be considered part of the gold standard in abdominally based free flap breast reconstruction.